SMRT Sequencing Reveals Candidate Genes and Pathways With Medicinal Value in Cipangopaludina chinensis - Zhou, Kangqi; Chen, Zhong; Du, Xuesong; Huang, Yin; Qin, Junqi; Wen, Luting; Pan, Xianhui; Lin, Yong (Frontiers in Genetics, 2022)
Cipangopaludina chinensis is an economically important aquatic snail with high medicinal value. However, molecular biology research on C. chinensis is limited by the lack of a reference genome, so the analysis of its transcripts is an important step to study the regulatory genes of various substances in C. chinensis. Herein, we conducted the first full-length transcriptome analysis of C. chinensis using PacBio single-molecule real-time (SMRT) sequencing technology. We identified a total of 26,312 unigenes with an average length of 2,572 bp, of which the largest number of zf-c2h2 transcription factor families (120,18.24%) were found, and also observed that the majority of the 8,058 SSRs contained 4-7 repeat units, which provided data for subsequent work on snail genetics Subsequently, 91.86% (24,169) of the genes were successfully annotated to the four major databases, while the highest homology was observed with Pomacea canaliculata. Functional annotation revealed that the majority of transcripts were enriched in metabolism, signal transduction and Immune-related pathways, and several candidate genes involved in drug metabolism and immune response were identified (e.g. CYP1A1, CYP2J, CYP2U1, GST, ,PIK3, PDE3A, PRKAG). This study lays a foundation for future molecular biology research and provides a reference for studying genes associated with the medicinal value of C. chinensis.